LMS Quasi-Newton and RLS Algorithms with Sparsity-Aware Updates applied to Communications - Ferreira, Tadeu N.; Lima, Markus V. S.; de Campos, Marcello L. R.; Diniz, Paulo S. R. (International Symposium on Wireless Communication Systems, 2024)
In this paper, constrained optimization methods with a sparsity-aware Newton-type direction update are applied to adaptive filtering. Different versions of the proposed algorithms, which include a sparsity-aware RLS and a CG algorithm, present lower computational complexity than traditional algorithms based on LMS-Newton, since the proposed algorithms require the use of a smaller Hessian estimate. The proposed algorithms are tested in acoustic echo cancellation and time-varying channel identification. Some of them present a computational reduction of 25% of that of the traditional LMS-Newton in the best case scenario. Most of the proposed algorithms present faster convergence than the benchmark algorithms in several scenarios.